(untitled) (Muse, 2025)
This study examines Gian Carlo Menotti’s opera buffa The Telephone, a work that stages the tension between the protagonist, Ben, and the Telephone, which assumes the role of co-protagonist and rival in the pursuit of Lucy. By combining different methodological perspectives – namely, those of Music Analysis and philosophical reflection on time and emotions – and drawing on the theories of philosophers such as Jankélévitch and Levinas, the study employs The Telephone as a case study to investigate the materialisation of scenic-musical time. In this opera, Menotti articulates the interplay between the temporalities of desire, waiting, and action, leading to their resolution in the final scene. There, the time of reconciliation is embodied in the waltz, which signifies not only the temporality of love and eros but also the act of agàpe — a time of unconditional giving – and the experience of the Other (Autrui) in the Levinasian sense. Ultimately, at the close of the opera, Ben recognises the Other in his rival, thereby opening a space for empathy and authentic relationality, transcending mere competition and achieving a form of human communion.